An Oligopoly Market Analysis in the Food and Beverage Sector Using Game Theory - Alqahtani, Ammar; Makki, Anas (Journal of King Abdulaziz University: Engineering Sciences, 2023)
Food and beverage production firms are socially active workplaces by their very nature. They function in an oligopoly market environment with their competitors. Conflicting interests of competitors create tradeoff game situations that impact many business decisions. The purpose of this paper is to conduct an oligopoly market analysis in the food and beverage sector using game theory. Data from two leading competing brands in the industry were collected for analysis. Five social interaction-related decisions were the focus of this study: marketing campaigns, price war, investment in R&D, the introduction of a new product, and a new policy. The designed games were based on the Prisoner's Dilemma, Deadlock, and Extensive-Form game models. Games, players, strategies (actions), assumptions (payoffs), representations, analysis, and results are addressed in a series of phases for each of the five studied decisions. Implications of this study include assisting decision-makers in the food and beverage industry in developing reactive and proactive strategies for competitor actions and maintaining competitive advantage.